Carbon-nickel magnesium aluminum hydrotalcite composite catalyst and preparation method and application thereof
Patent Information
- Application Number
- CN202410455476.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-16
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-04-16
AI Technical Summary
[0004]如专利CN105195154A公开的一种生物质解聚产物重整制氢催化剂及其制备方法,虽然采用共沉淀合成水滑石,但是所制水滑石催化剂反应活性时间太低,氢气产量不高
[0025](1)本发明采用制备过程简便且成本低廉的镍镁铝类水滑石催化剂,通过引入有机碳源的方式,在保持水滑石催化剂尖晶石结构的同时在其中形成了特殊的碳-镍结构,增加了结构的稳定性,在进行了十七次循环反应后(反应总时长大于100h),产氢量损失控制在35%以内。
Smart Images

Figure CN118287060B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aqueous reforming hydrogen production technology, and in particular to a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst, its preparation method, and its application. Background Technology
[0002] Compared to the commonly used steam reforming method, aqueous reforming for hydrogen production can react with the substrate at a lower temperature, eliminating the need for high-temperature gasification, resulting in lower energy consumption. Furthermore, it provides a certain pressure, facilitating subsequent hydrogen adsorption and purification. Currently, aqueous reforming catalysts generally suffer from poor hydrothermal stability and susceptibility to destructive degradation, thus limiting their large-scale commercial application.
[0003] The commonly used commercial aqueous reforming catalyst for hydrogen production is the noble metal catalyst Pt / Al2O3, but the use of the noble metal Pt results in a high overall cost of hydrogen production. Non-noble metal catalysts, such as nickel-magnesium-aluminum layered double hydroxide catalysts, can achieve high aqueous reforming activity and hydrogen selectivity at a low price.
[0004] For example, patent CN105195154A discloses a catalyst for hydrogen production through reforming of biomass depolymerization products and its preparation method. Although it uses co-precipitation to synthesize hydrotalcite, the resulting hydrotalcite catalyst has a low reaction activity time and low hydrogen yield. CN102417161B discloses a method for producing CO-free hydrogen through steam reforming of biomass alcohols. While the catalyst exhibits good performance in steam reforming hydrogen production, the steam reforming reaction temperature is high, resulting in high energy consumption. Furthermore, even if the carbon monoxide content in the gaseous product is extremely low, the gaseous product contains a large amount of carbon dioxide and alkane byproducts. Additionally, the gaseous product after steam reforming is not easily purified into hydrogen through adsorption. CN105536801B discloses a Ni-based composite catalyst, its preparation method, and its application. Although it uses hydrotalcite and carbon to synthesize a Ni-based composite catalyst, it mainly utilizes the complementary characteristics of Ni-based and carbon-based catalysts in the reforming reaction.
[0005] In summary, existing Ni-based catalysts suffer from drawbacks such as low structural stability, high methanation activity, and low hydrogen selectivity. Furthermore, the carbon dioxide produced during the reaction dissolves in water, causing the active component nickel to leach out and damage the catalyst structure, reducing the activity of the nickel-magnesium-aluminum layered double hydroxide catalyst and hindering stable and efficient hydrogen production. Summary of the Invention
[0006] This invention provides a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst, its preparation method, and its application, with the aim of solving the aforementioned problems existing in the background art.
[0007] To achieve the above objectives, embodiments of the present invention provide a carbon-nickel-magnesium-aluminum layered double hydroxide (LDH) composite catalyst, its preparation method, and its application. By introducing an organic carbon source to modify the LDH catalyst, a certain proportion of organic carbon source is incorporated into the catalyst to form defect sites on the catalyst surface. The resulting catalyst retains the original LDH structure while forming nickel particle clusters dominated by a special carbon-nickel structure. On the one hand, this increases the specific surface area of the catalyst, increasing the contact area between the exposed active metal Ni and the raw material methanol, improving the utilization rate of the active metal, and promoting the adsorption and dehydrogenation of methanol on Ni. On the other hand, the special carbon-nickel structure enhances the interaction between Ni and the support, inhibiting the oxidation, aggregation, and leaching of nickel, and is beneficial for promoting the adsorption and activation of the raw gas by the catalyst, thereby improving the catalyst activity and hydrogen production. The hydrophilic carbon component in the catalyst promotes the adsorption of water, which is beneficial for promoting the water-gas shift reaction. The nickel-magnesium-aluminum layered double hydroxide (LDH) catalyst used in this invention, specifically for alkaline co-processing, achieves a significant improvement in catalyst activity and hydrogen selectivity by controlling the amount of organic carbon source introduced during catalyst preparation and calcining the catalyst at high temperature for a specified time. This results in catalysts with different microstructures. Simultaneously, this invention increases the dispersion of the catalytically active metal, improving the catalyst efficiency. In aqueous reforming experiments, the single-batch hydrogen production exceeds 270 mmol / g, achieving a significant increase in hydrogen production at low cost. Furthermore, carbon modification significantly improves the catalyst's stability; after more than 100 hours of cycling, the hydrogen production still reaches over 70% of the maximum value. Moreover, the proposed method of modifying the catalyst with organic carbon source-doped LDH can suppress defects such as easy sintering and structural collapse leading to deactivation in nickel-magnesium-aluminum LDH catalysts, improving catalyst performance and extending catalyst lifespan by up to three times while increasing hydrogen production in aqueous reforming reactions.
[0008] The present invention provides a method for preparing a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst, comprising the following steps:
[0009] S1. Dissolve an appropriate amount of nickel metal salt, magnesium metal salt, aluminum metal salt and organic carbon source in an appropriate amount of deionized water, and stir thoroughly at room temperature until completely dissolved to obtain a salt solution;
[0010] S2. Dissolve an appropriate amount of alkaline substance in an appropriate amount of deionized water to obtain an alkaline solution;
[0011] S3. Under vigorous stirring, the alkaline solution and salt solution are slowly dripped into a strongly alkaline environment at the same rate. The mixture is stirred thoroughly under high temperature conditions while maintaining the alkaline environment to ensure the formation of the hydrotalcite structure. A co-precipitation reaction occurs. The suspension is filtered, washed with deionized water, and dried to obtain a carbon-nickel-magnesium-aluminum hydrotalcite precursor.
[0012] S4. The carbon-nickel magnesium aluminum hydrotalcite precursor is calcined at high temperature in a muffle furnace for a certain time to undergo topological transformation and obtain carbon-nickel magnesium aluminum hydrotalcite carrier.
[0013] S5. The carbon-nickel-magnesium-aluminum hydrotalcite support is reduced and activated at high temperature in a tube furnace for a certain time to obtain a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst.
[0014] By doping organic carbon sources during the synthesis of hydrotalcite, CO2 will be released during further calcination, thereby forming more mesoporous structures on the surface of hydrotalcite. The formation of pore structures is beneficial for the catalyst to capture the reaction substrate in the solution, thus promoting the reaction.
[0015] Preferably, in step S1: the nickel metal salt is at least one of nickel nitrate, nickel chloride, nickel acetate, nickel carbonate, nickel nitrous nitrate, nickel sulfide, nickel cyanide, and nickel oxalate; the magnesium metal salt is at least one of magnesium nitrate, magnesium chloride, magnesium acetate, magnesium carbonate, magnesium nitrous nitrate, magnesium sulfide, magnesium cyanide, and magnesium oxalate; the aluminum metal salt is at least one of aluminum nitrate, aluminum chloride, aluminum acetate, aluminum carbonate, aluminum nitrous nitrate, aluminum sulfide, aluminum cyanide, and aluminum oxalate; M(Ⅲ) / M(Ⅲ+Ⅱ) = 0.28 (the molar concentration ratio of trivalent metal ions to the total amount of trivalent and divalent metal ions); the organic carbon source is at least one of citric acid, glucose, sorbitol, malic acid, fructose, and sucrose; and M(C) / M (the mass ratio of organic carbon source to metal oxide) is 0-100% and not zero.
[0016] Preferably, the alkaline substance in step S2 is at least one of sodium bicarbonate, potassium hydroxide, sodium carbonate, and sodium hydroxide; the amount of alkaline substance added is 2-15g.
[0017] Preferably, in step S3: the pH value of the strongly alkaline environment is 10-11; the high temperature during high-temperature stirring is 303-403K, and the stirring time is 12-24h; the deionized water is used to rinse until the pH value is 6-8, the drying temperature is 323-423K, and the drying time is 6-18h.
[0018] Preferably, the high temperature in step S4 is 723–823 K, and the calcination time is 1–3 h.
[0019] Preferably, the high temperature in step S5 is 723–823 K, and the reduction time is 1–3 h.
[0020] Based on a general inventive concept, embodiments of the present invention provide a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst prepared by the above-described preparation method.
[0021] Preferably, the catalyst has a porous C-Ni cluster structure with an average specific surface area of 162.31 m². 2 / g.
[0022] The embodiments of the present invention also provide the application of the carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst prepared by the above preparation method or the above carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst in methanol aqueous reforming for hydrogen production.
[0023] Preferably, after multiple cycles of the methanol aqueous reforming reaction, the H2 yield remains above 70% of the initial reaction yield.
[0024] The above-described solution of the present invention has the following beneficial effects:
[0025] (1) The present invention uses nickel-magnesium-aluminum hydrotalcite catalysts that are easy to prepare and have low cost. By introducing an organic carbon source, a special carbon-nickel structure is formed in the hydrotalcite catalyst while maintaining the spinel structure, which increases the stability of the structure. After seventeen cycles of reaction (total reaction time greater than 100h), the loss of hydrogen production is controlled within 35%.
[0026] (2) The present invention uses hydrotalcite doped with organic carbon source to modify the catalyst, so that the CO2 generated during the calcination process forms pores on the catalyst surface, thereby increasing the surface area of the catalytically active metal nickel. In the aqueous reforming reaction experiment, the single hydrogen production is greater than 270 mmol / g, which is 85% higher than that of the carbon-free modified catalyst, and the hydrogen production is greatly increased at low cost.
[0027] (3) The present invention significantly improves the hydrothermal stability of the nickel-based catalyst for aqueous reforming hydrogen production, with better catalyst cycle life and higher hydrogen production, and the performance and overall economy of aqueous reforming hydrogen production are improved. Attached Figure Description
[0028] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0029] Figure 1 This is a TEM characterization image of the carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst of the present invention.
[0030] Figure 2 This invention relates to embodiments of the carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst and the catalytic reaction effects of different carbon ratios.
[0031] Figure 3 This is a TEM characterization image of the carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst after the aqueous reforming cycle reaction of the present invention.
[0032] Figure 4This is a graph showing the hydrogen production and gas ratio in the aqueous reforming cycle reaction of the carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst of the present invention.
[0033] Figure 5 This is a TEM characterization image of the nickel-magnesium-aluminum hydrotalcite catalyst of Comparative Example 1 of the present invention.
[0034] Figure 6 These are the N2 adsorption-desorption isotherms of the carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst of Example 1 and the nickel-magnesium-aluminum hydrotalcite catalyst of Comparative Example 1 of the present invention. Detailed Implementation
[0035] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.
[0036] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0037] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0038] This invention addresses existing problems by providing a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst, its preparation method, and its application.
[0039] Example 1
[0040] A method for preparing a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst includes the following steps:
[0041] (1) Dissolve appropriate amounts of Ni(NO3)2·6H2O, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and citric acid together in 50 mL of deionized water, where M(Ⅲ) / M(Ⅲ+Ⅱ)=0.28 (the ratio of trivalent metal ions to the total amount of trivalent and divalent metal ions in the salt solution, with metal ions expressed in molar concentration mol / L), and M(C) / M (mixed oxides) (NiO, MgO, Al2O) is 20%. Stir thoroughly at room temperature until completely dissolved, and this solution is considered as a salt solution.
[0042] (2) Weigh out a certain amount of Na2CO3 and NaOH and dissolve them in 50 mL of deionized water. This solution is called an alkaline solution.
[0043] (3) Under vigorous stirring, the above alkaline solution and salt solution were slowly added dropwise to a strongly alkaline environment with a pH of 10-11 at the same rate. Then, the mixture was stirred at 303K for 24 hours, during which the pH remained between 10 and 11. The suspension was filtered, washed with deionized water until neutral (pH = 6-8), and then dried at 373K for 18 hours to obtain the hydrotalcite precursor.
[0044] (4) The hydrotalcite precursor was calcined in a muffle furnace at 823K for 1h to obtain C-nickel magnesium aluminum hydrotalcite carrier.
[0045] (5) The C-nickel-magnesium-aluminum layered double hydroxide (LDH) support was reduced and activated in a tube furnace at 823 K for 2 h to synthesize a C-nickel-magnesium-aluminum LDH composite catalyst, with 20% C-NiMgAl content (20% represents the nominal C loading). The carbon-nickel-magnesium-aluminum LDH composite catalyst prepared in Example 1 was applied to methanol aqueous reforming for hydrogen production. The reaction was carried out in a high-pressure metal reactor. The reactor contained a methanol solution, and the system pressure was adjusted using N2. The reaction temperature was set between 210 and 240 °C, the reaction pressure between 1.95 and 6.0 MPa, and the reaction time between 3 and 18 h. The C-NiMgAl composite catalyst was added at a rate of 10 g / L for experiments and tests.
[0046] Example 2
[0047] A method for preparing a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst differs from Example 1 in that the C loading is 40%.
[0048] Example 3
[0049] A method for preparing a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst, which differs from Example 1 in that the C loading is 60%.
[0050] Example 4
[0051] A method for preparing a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst differs from Example 1 in that the C loading is 80%.
[0052] Example 5
[0053] A method for preparing a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst, which differs from Example 1 in that the C loading is 100%.
[0054] Example 6
[0055] A method for preparing a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst differs from Example 1 in that the calcination time in the muffle furnace is 2 hours.
[0056] Example 7
[0057] A method for preparing a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst differs from Example 1 in that the calcination time in the muffle furnace is 3 hours.
[0058] Comparative Example 1
[0059] A method for preparing a nickel-magnesium-aluminum hydrotalcite catalyst differs from Example 1 in that the C loading is 0.
[0060] Comparative Example 2
[0061] A method for preparing a carbon-nickel-magnesium-aluminum hydrotalcite catalyst differs from Example 1 in that the C loading is 120%. In this comparative example, the methanol conversion rate is less than 3%, and almost no gaseous substances are produced. Therefore, it can be considered that the organic carbon source doping content is too high, and the hydrotalcite structure cannot be formed. The prepared catalyst does not have catalytic activity.
[0062] Comparative Example 3
[0063] A method for preparing a nickel-magnesium-aluminum hydrotalcite catalyst differs from Example 1 in that it is calcined in a nitrogen furnace. The gaseous products generated after the reaction are less than 50% of those in Example 1 and have poor stability; therefore, the quality of this catalyst is considered significantly inferior to that of Example 1.
[0064] Comparative Example 4
[0065] A method for preparing a nickel-magnesium-aluminum hydrotalcite catalyst differs from Example 1 in that it is calcined in a hydrogen furnace. The gaseous products generated after the reaction are approximately 90% of those in Example 1, but the proportion of hydrogen in the gaseous products is extremely low, less than 30%. Therefore, it is considered that the hydrogen selectivity of this catalyst is significantly worse than that of the example.
[0066] The catalyst was characterized by TEM before and after the reaction. The catalyst before the reaction was as follows: Figure 1 As shown, the carbon-modified Ni-based catalyst forms Ni particle clusters with a predominantly nickel-carbon structure. On the one hand, this structure enhances the interaction between nickel and the support, making it less prone to Ni particle aggregation and leaching during the reaction. On the other hand, the Ni particles in the catalyst are more uniformly dispersed. Statistical analysis of the average particle size distribution of Ni particles showed that the average Ni particle size in Example 1 was 3.55 nm, significantly smaller than that of the carbon-free catalyst (4.08 nm). This implies that the catalyst surface exposes more active sites, and the leaching of these active sites is inhibited as the reaction proceeds, thereby improving the catalyst's catalytic activity and stability.
[0067] Figure 2This figure shows the reaction effects of catalysts with different carbon ratios. The bar chart on the left (y-axis) represents the content of each component in the gaseous products after reaction per unit mass of catalyst with different carbon ratios. It can be seen that the carbon-nickel-magnesium-aluminum catalyst with 80% carbon content has the highest hydrogen production, significantly higher than other groups, at 276.21 mmol / g, with a hydrogen production per unit time of 43.04 mmol / (h·g), far exceeding that of the unmodified catalyst (143.42 mmol / g). The dotted line graph on the right (y-axis) represents the proportion of hydrogen in the gaseous products (hydrogen selectivity). It can be seen that the carbon-nickel-magnesium-aluminum catalyst with 80% carbon content has the highest hydrogen selectivity of 76.24%, while the yield of the impurity gas CO is extremely low, less than 3 ppm.
[0068] from Figure 3 The TEM characterization results show that after seventeen cycles, the Ni particle clusters, predominantly C-Ni, in the Ni-based catalyst remain stable, effectively suppressing Ni particle leaching and maintaining good Ni particle dispersion. This indicates that the catalyst possesses excellent cycle stability. Figures 3-4 It was observed that after 17 methanol APR reaction cycles, the 80% C-NiMgAl catalyst exhibited good stability, with the H2 yield gradually decreasing during the cycles but still remaining above 70% of the initial reaction yield. This stability may be attributed to the formation of Ni clusters facilitated by carbon doping, which enhances interactions and reduces Ni dissolution. However, with increasing cycle number, the methane yield decreased significantly, mainly due to a reduction in overall gas production. In the cyclic reaction, the CO yield was extremely low, with the CO content in the gas produced during any single reaction cycle being less than 3 ppm, indicating that the water-gas shift reaction proceeded sufficiently. CO2 production was affected by various factors, including changes in total gas production, reaction conditions, and catalyst state, but overall remained relatively stable.
[0069] from Figure 5 TEM characterization images show that the nickel particles in the nickel-based layered double hydroxide catalyst of Comparative Example 1, which was not modified with an organic carbon source, are randomly distributed and poorly dispersed. During the aqueous reforming reaction, they are prone to aggregation and leaching, leading to catalyst deactivation. Therefore, the nickel-based layered double hydroxide catalyst without organic carbon source modification has a short service life (less than 30 hours).
[0070] from Figure 6The N2 adsorption-desorption isotherms demonstrated confirm the porous structure of the catalyst. Both NiMgAl and C-NiMgAl samples exhibited type IV isotherms and H2-type hysteresis loops. Based on these characteristics, it can be determined that the C-NiMgAl sample possesses a more mesoporous structure due to the partial vaporization and precipitation of carbon components (the International Union of Pure and Applied Chemistry (IUPAC) classifies pores in powder materials according to size as micropores (pore size < 2 nm) and mesopores (pore size 2–50 nm)). The average specific surface area (SBET) of the C-NiMgAl sample (represented by 80% C-NiMgAl) is 162.31 m². 2 / g, compared to the NiMgAl sample (139.43m 2 The surface area ( / g) of the catalyst is significantly improved, thanks to the smaller grain size after carbon doping. Carbon-doped NiMgAl catalysts are not only simple to operate and inexpensive, but also exhibit a higher specific surface area, thus showing a clear advantage over pure NiMgAl catalysts.
[0071] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. The application of a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst in methanol aqueous reforming for hydrogen production, characterized in that, The preparation method of the catalyst includes the following steps: (1) Dissolve appropriate amounts of Ni(NO3)2·6H2O, Mg(NO3)2·6H2O, Al(NO3)3·9H2O and citric acid together in 50 mL of deionized water. The ratio of trivalent metal ions to the total amount of trivalent and divalent metal ions in the salt solution is 0.
28. The metal ions are expressed in molar concentration (mol / L). The ratio of M(C) / M (mixed oxides) is 80%. Stir thoroughly at room temperature until completely dissolved. This solution is called the salt solution. The mixed oxides are NiO, MgO and Al2O3. (2) Weigh out a certain amount of Na2CO3 and NaOH and dissolve them in 50 mL of deionized water. This solution is called an alkaline solution. (3) Under vigorous stirring, the above alkaline solution and salt solution were slowly added dropwise to a strongly alkaline environment with a pH of 10-11 at the same rate. Then, the mixture was stirred at 303K for 24 hours. During this process, the pH was maintained between 10 and 11. The suspension was filtered, washed with deionized water until neutral, and then dried at 373K for 18 hours to obtain the hydrotalcite precursor. (4) The hydrotalcite precursor was calcined in a muffle furnace at 823K for 1h to obtain C-nickel magnesium aluminum hydrotalcite carrier; (5) The C-nickel-magnesium-aluminum hydrotalcite support was reduced and activated in a tube furnace at 823K for 2h to synthesize a carbon-nickel-magnesium-aluminum hydrotalcite composite catalyst with 80% C-NiMgAl, where 80% represents the nominal C loading.
2. The application according to claim 1, characterized in that, After 17 cycles of methanol aqueous reforming, the H2 yield remained above 70% of the initial reaction yield.
Citation Information
Patent Citations
Method for producing CO-free hydrogen by steam reformation based on biomass alcohol as raw material
CN102417161B
Biomass depolymerized product reforming hydrogen production catalyst and preparation method thereof
CN105195154A
A Ni-based composite catalyst, its preparation method and application
CN105536801B
Method for hydrogen production by promoting water-phase reforming of recyclable biomass alcohol derivatives through alkali liquor
CN116902916A
